2022
DOI: 10.1002/ijgo.14306
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester screening for pre‐eclampsia and small for gestational age: A comparison of the gaussian and Fetal Medicine Foundation algorithms

Abstract: Objective: Pre-eclampsia (PE) and small for gestational age (SGA) can be predicted from the first trimester. The most widely used algorithm worldwide is the Fetal Medicine Foundation (FMF) algorithm. The recently described Gaussian algorithm has reported excellent results although it is unlikely to be externally validated. Therefore, as an alternative approach, we compared the predictive accuracy for PE and SGA of the Gaussian and FMF algorithms.Methods: Secondary analysis of a prospective cohort study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…There is ongoing debate regarding which risk factors to include and the type of measures that should be part of risk assessment strategies [ 43 ]. Clinical practice guidelines (CPGs) recommend a combination of predictive assessments that include clinical risk factors, biophysical markers such as MAP and UtAPI, and biochemical markers such as pregnancy-associated plasma protein A (PAPP-A) and/or PlGF [ 44 , 45 ]. Various combinations of these measures are advised by different national bodies and professional societies [ 32 , 43 , 46 ].…”
Section: Evidence For the Increased Risk Of Pe In Women With Pcos And...mentioning
confidence: 99%
“…There is ongoing debate regarding which risk factors to include and the type of measures that should be part of risk assessment strategies [ 43 ]. Clinical practice guidelines (CPGs) recommend a combination of predictive assessments that include clinical risk factors, biophysical markers such as MAP and UtAPI, and biochemical markers such as pregnancy-associated plasma protein A (PAPP-A) and/or PlGF [ 44 , 45 ]. Various combinations of these measures are advised by different national bodies and professional societies [ 32 , 43 , 46 ].…”
Section: Evidence For the Increased Risk Of Pe In Women With Pcos And...mentioning
confidence: 99%
“…First and second trimester screening strategies have been developed following rigorous preclinical, case control, observational, intervention, and real-world evaluation studies [9,10]. These screening models have been found to have good predictive value for early diagnosis of some obstetric syndromes, such as pre-eclampsia (PE) and fetal growth restriction (FGR), and result in increased surveillance of all women identified as high-risk [10,11]. Multivariate screening can be performed at 11-14 weeks gestation using a combination of maternal, biophysical, and serum biochemical markers [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Gaussian algorithm was designed to predict early-onset PE; however, it has shown a similar performance to that of the Fetal Medicine Foundation algorithm for predicting preterm PE, early-onset PE and small for gestational age (SGA) fetuses in a Spanish population. 11 The ASPRE trial showed that daily administration of 150 mg of salicylic acid (ASA) before 16 weeks reduces the incidence of preterm PE by 62% and may also reduce the incidence of early-onset PE, early-onset SGA and preterm SGA by 82%, 40% and 20%, respectively. 12 These favorable findings were observed in a research context; however, a screening strategy may be less effective in real-life clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in most Spanish maternities the Gaussian algorithm is used for routine screening in the first trimester, as it allows assessment of the UtAPI by Doppler ultrasound either transabdominally or transvaginally, and measurement of the biomarkers between 8 +0 and 13 +6 weeks, 10 rendering it easy to integrate with the first‐trimester aneuploidy screening, and highly adaptable in different settings. The Gaussian algorithm was designed to predict early‐onset PE; however, it has shown a similar performance to that of the Fetal Medicine Foundation algorithm for predicting preterm PE, early‐onset PE and small for gestational age (SGA) fetuses in a Spanish population 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation